Quantitative Comparison of Fibrin Degradation with Plasmin, Miniplasmin, Neurophil Leukocyte Elastase and Cathepsin G - Kolev, Krasimir; Komorowicz, Erzsébet; Owen, Whyte G; Machovich, Raymund (Thrombosis and Haemostasis, 1996)
The relative contribution of plasmin, miniplasmin, PMN-elastase and cathepsin G to the fibrin-gel dissolution is studied. The global kcat/KM ratios are determined as a measure of the fibrinolytic catalytic efficiency using spectrophotometric kinetic analysis of the competition between fibrin and synthetic peptide substrates for the proteases, turbi-dimetric assay for fibrin dissolution and gel-filtration of the partially degraded fibrin. When the substrate is fibrin polymerized in the presence of 3 mM Ca2+, the value of this ratio is 4.3 × 105 M-1·s-1 for plasmin, 1.9 × 105 M-1·s-1 for miniplasmin, 5.0 × 104 M-1·s-1 for PMN-elastase and 2.2 × 103 M-1·s-1 for cathepsin G. When fibrin is polymerized without addition of Ca2+, the kcat/KM values are increased by a factor of 2.3 for plasmin, 2.0 for miniplasmin and 1.6 for cathepsin G, whereas that of PMN-elastase is unchanged. Progressive crosslinking of fibrin decreases the catalytic action of all studied proteases, but no change in their relative contribution to fibrinolysis is observed. When plasmin inhibitor (at physiological concentration) is also crosslinked to fibrin, the most efficient fibrinolytic enzymes are miniplasmin and PMN-elastase. The effect of 6-aminohexanoate on the formation of fibrin degradation products by plasmin and miniplasmin suggests that the high-affinity lysine binding site in the N-terminal kringle domain of plasmin is involved in the interactions with the native polymerized fibrin, whereas the fifth kringle found in both enzymes participates in binding to newly exposed lysine residues. These results provide a quantitative basis for the evaluation of fibrinolytic efficiency and support the concept of synergistic fibrinolysis.